Solitary Fibrous Tumor of the Urinary Bladder - Limsirilak, Tanalak (Health Science Clinical Research, 2023)
ABSTRACT Introduction: Solitary fibrous tumor (SFT) is a rare fibroblastic tumor characterized by pathognomonic NAB2-STAT6 gene fusion on chromosomal region 12q13. It occurs at any anatomical site,including superficial and deep soft tissues and within visceral organs. SFT of urinary bladder is quite rare. In this study, the author presents SFT of urinary bladder case with immunophenotypes and English literature reviews. There are 27 cases, divided into a patient receiving treatment and 26 case studies from relevant English literature reviews. Case presentation: A 45-year-old Thai man presented with progressive lower abdominal pain. Physical examination revealed an intra-abdominal mass palpated in left lower quadrant. A subsequent computed tomography of his abdomen revealed a 5.6x5.1 cm. circumscribed enhancing mass arising from left sided urinary bladder base. He underwent operative transurethral resection of bladder tumor and radical cystectomy. The cut surface of resected urinary bladder revealed a 4x2.5x2.2 cm. homogenous white-tan mass-like lesion located in the bladder trigone. A histologic evaluation revealed haphazard proliferation of spindle cells with fine nuclear chromatin. Staghorn-like blood vessels are frequently observed in dense collagenous stroma. The histological features combined with immunohistochemical studies were suggestive of solitary fibrous tumor that appeared to be growing from submucosa of the urinary bladder. He is currently four months post-surgery without evidence of metastasis or recurrence. Conclusion: SFT of urinary bladder comprise a histologic features of mesenchymal neoplasms that show fibroblastic differentiation. The clinical presentations were variable and non-specific. Immunohistochemical studies played an important role for diagnosis and differentiating SFT from other spindle cell mesenchymal tumors. Prognostic factors are age, tumor size, mitotic figure, focal necrosis, and surgical margin status. Clinical and biological behaviors are usually benign and can be predicted based on the pathological features. Complete surgical resection is the gold standard of treatment. Chemotherapy and adjuvant radiation therapy can be considered in case of nonresectable tumor or metastasis. Keywords: Solitary fibrous tumor, Urinary bladder, STAT6, CD34